How Crawling and Manual Object Exploration are Related to the Mental Rotation Abilities of 9-Month-Old Infants - Schwarzer, Gudrun; Freitag, Claudia; Schum, Nina (Frontiers in Psychology, 2013)
The present experiment examined whether the mental rotation ability of 9-month-old infants was related to their abilities to crawl and manually explore objects. Forty-eight 9-month-old infants were tested; half of them had been crawling for an average of 9.3 weeks. The infants were habituated to a video of a simplified Shepard-Metzler object rotating back and forth through a 240° angle around the longitudinal axis of the object. They were tested with videos of the same object rotating through a previously unseen 120° angle and with a mirror image of the display. All of the infants also participated in a manual object exploration task, in which they freely explored 5 toy blocks. The results showed that the crawlers looked significantly longer at the novel (mirror) object than at the familiar object, independent of their manual exploration scores. The non-crawlers looking times, in contrast, were influenced by the manual exploration scores. The infants who did not spontaneously explore the toy blocks tended to show a familiarity preference, whereas those who explored the toy blocks preferred to look at the novel object. Thus, all of the infants were able to master the mental rotation task but it seemed to be the most complex process for infants who had no crawling experience and who did not spontaneously explore objects.